Coordination Compounds Of Calcium Acetate With Some Ligands (Texas Journal of Engineering and Technology, 2023)
The synthesis of mixed-ligand coordination compounds of calcium magnesium acetates with formamide, acetamide, benzamide, benzoic and nicotinic acid was carried out. The composition, individuality, methods of coordination of amide molecules and fragments of anions of acetic and nicotinic acids have been established. The thermal behavior of the synthesized coordination compounds has been studied. The compositions, temperature ranges of thermal effects, quantitative changes in the mass of stages, and the nature of the final thermolysis product were determined. The most effective concentrations of complex compounds have been established in terms of their effect on the germination energy and germination of cotton seeds in a laboratory experiment.